Application of FTIR spectroscopy in determining sesamol in sesame seed oil - Mirghani, Mohamed Elwathig Saeed; Che Man, Yakoob; Jinap, Selamat; Baharin, B. S.; Bakar , Jamilah (Springer Berlin, 2003)
A new analytical method was developed for determining sesamol in sesame seed oil by FTIR spectroscopy. Sesamol was also spiked at 0 to 1000 mg/kg in freshly refined, bleached, and deodorized palm olein (RBDPOo) and groundnut (peanut) oil. FTIR spectra were recorded using a transmission (NaCl) cell accessory at room temperature, and the partial least squares regression statistical method was used to derive calibration models for each oil. The standard errors of calibration were 6.07, 5.88, and 4.24 mg/100 g for sesame, RBDPOo, and groundnut oils, with coefficients of determination (R2) of 0.9947, 0.9940, and 0.9662, respectively. The calibration models were validated by the “leave-one-out” cross-validation method, and the R2 of validation, the standard errors of prediction, and SD of the differences for repeatability and accuracy were computed. Our results support the premise that FTIR spectroscopy is an efficient and accurate method for determining minor components such as sesamol in edible oils. Paper no. J10132 in JAOCS 80, 1–4 (January 2003).